ROLE OF CONVENTIONAL AND DIGITAL RADIOGRAPHY IN APICAL ROOT RESORPTIONS DIAGNOSTIC - Anca Melian (Romanian Journal of Medical and Dental Education, 2019)
The study aimed to determine the diagnostic possibilities of incipient apical root resorptions and the diagnostic sensibility of the conventional and digital radiography for small, medium and large apical root resorptions. To achieve this goal, it was performed an in vitro radiographic follow-up study on simulated root resorption cavities and a clinical and radiographic study on a patient’s group with chronic periapical lesions. Conventional radiography can be used as a reliable exam for early detection of medium and large root resorption cavities located in apical third. Digital radiography has higher sensitivity values for medium and large root resorption cavities. Detection percent for small radicular resorption cavities is inferior for both conventional and digital radiography. All periapical lesions can be considered an important etiological factor for the incipient, medium and severe external radicular resorptions. Radicular cysts and periapical diffuse osteitis represent potential etiological factors for severe apical root resorptions.